In Vitro Comparison of Microleakage, Marginal Fit, and Cement Thickness of Conventional and Prepless Lithium Disilicate Veneers - Pierre, Fernanda Zapater [UNESP]; Demachkia, Amir Mohidin [UNESP]; Tanaka, Lucas Eigi Borges [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Araujo, Rodrigo Maximo de [UNESP]; Silva, Joao Mauricio Ferraz da [UNESP] (Quintessence Publishing Co Inc, 2023)
Purpose: To assess the influence of two preparation techniques on the microleakage, marginal fit, and cement thickness of lithium disilicate veneers. Materials and Methods: A total of 24 human maxillary central incisors were divided randomly into two groups according to preparation technique (n = 12 each): a minimally invasive preparation with a butt-joint design (0.3-mm depth) and a chamfer finish line (group MP); and no preparation (group NP). All teeth were restored with lithium disilicate veneers cemented with photopolymerizable resin cement. Specimens were aged thermally (6,000 cycles of 5 degrees C to 55 degrees C) and mechanically (100,000 cycles at 100 N, 4 Hz). Specimens were immersed in fuchsin dye for 24 hours using a standard dye penetration technique, then sectioned and evaluated under a stereomicroscope (x20 magnification). Data were analyzed by ANOVA and Kruskal-Wallis tests (P < .05). Results: There was significant microleakage (P = .0163) at the cervical area compared to the proximal area. The marginal fit was similar, with no statistical difference (P = .212) between groups MP (153 +/- 81 pm) and NP (111 +/- 74 pm). Group MP showed a significantly (P= .006) reduced cement thickness at the cervical area (87 +/- 27 pm) compared to group NP (210 +/- 89 pm). Conclusion: Although the preparation technique was shown to influence the cement thickness, it did not show any influence on microleakage or marginal fit. Intl Prosthodont 2023;36:63-70. doi: 10.11607/ijp.7616